Diversity of Zooplankton in the Kandis River Karya Indah Village, Tapung Sub-Regency, Kampar Regency, Riau Province - Sthepani, Sherly; ', Yuliati; ', Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A study on the diversity of zooplankton in the Kandis River was conducted from January 2014. This research aims to understand the type and abundance of zooplankton in the Kandis River . There were three stations with 3 sampling points in each station. Samples were taken 3 times, once a week and they were analyzed in the marine productivity Riau University.Result shown that the phytoplankton obtained were consist of 6 species, they were belonged to of 2 classes, namely Rotifera (4species), Cilliata (2 species). The average of fitoplankton abundance was around 220-319 ind/l. General water quality parameters are as follow: temperature: 290C, brightness: 30-32,5 cm, current speed: 0,08-0,12 m/s, pH: 5, DO: 35–3,7 mg/l, CO2: 11,88–12,9 mg/l.Keywords: Diversity. Zooplankton, Kandis River